The relationship between the effectiveness of preschools and leadership styles of school managers - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
This study aimed to analyze the relationship between the effectiveness of preschools and their managers' leadership styles, according to the opinions of teachers and managers from the preschool year of elementary schools and from independent kindergartens. The study had a descriptive nature. The study population included teacher and managers working in Istanbul. The sample consisted of 198 teachers and 67 managers chosen with random sampling from the districts of Kadikoy, Umraniye, Maltepe, Fatih, and Kartal in Istanbul. The Effective School Survey was utilized to measure the effectiveness of schools and the Multifactor Leadership Questionnaire-Evaluation Form to evaluate the leadership styles of managers. The results indicated a positive meaningful relationship (p<.01 and p<.05) between the subdimensions of the effective school survey and the multifactor leadership styles questionnaire. This finding is indicative of a parallel relationship between the effectiveness of schools and high leadership skills possessed by managers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Preschool education; manager; leadership; effective school; management